2020
DOI: 10.3389/fpls.2020.00846
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Spectral Light Composition Affects Chilling Injury in Anthurium Cut Flowers

Abstract: The effect of the lighting environment during postharvest storage of ornamentals has largely been neglected in previous research. Anthurium is a cold-sensitive species originating from tropical climates and is widely cultivated all around the world for its colorful spathes. To investigate the effects of light spectrum on the performance of Anthurium cut flowers under cold storage, two cultivars [Calore (red spathe) and Angel (withe spathe)] were placed at low temperature (4°C), either in darkness (D) or under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 62 publications
1
5
0
1
Order By: Relevance
“…The ratio of red spectrum ranged from 40 to 60%, with other light sources increasing the TSC and sugar in L7, L8, L9, and L10 (Figure 6). The monochromatic red, blue, and their combined spectra manifested decreased soluble carbohydrate in Anthurium cut flowers in a previous study [63]. Our present study also found a lower TSC and sucrose content in combined red-blue spectra compared to all other treatments.…”
Section: Discussionsupporting
confidence: 83%
“…The ratio of red spectrum ranged from 40 to 60%, with other light sources increasing the TSC and sugar in L7, L8, L9, and L10 (Figure 6). The monochromatic red, blue, and their combined spectra manifested decreased soluble carbohydrate in Anthurium cut flowers in a previous study [63]. Our present study also found a lower TSC and sucrose content in combined red-blue spectra compared to all other treatments.…”
Section: Discussionsupporting
confidence: 83%
“…The key CI symptoms of Anthuriumare 'Browning' and 'Blueing' of the spathes and wilting of spadixes (Promyou et al, 2012;Aghdam et al, 2015). Generally, storing Anthurium at an optimum temperature of 10-12°C controls these symptoms (Reid and Wu, 1992;Balas et al, 2006;Aliniaeifard et al, 2020). However, Paull (1987) found exceptions regarding the storage of some other Anthurium varieties at higher temperatures (14-17°C).…”
Section: Post-harvest Factorsmentioning
confidence: 99%
“…However, petal growth and vase life of cut roses changed when exposed to different light environments even without leaves (Horibe et al, 2020 ), indicating that responses of cut flowers to light stimuli cannot be explained only by the function of leaves. In addition, blue light resulted in shorter vase life in cut anthurium ( Anthurium andraeanum ) under cold storage and the negative effect of blue light was attributed to its effect on increased water loss and oxidative stress (Aliniaeifard et al, 2020 ). There are still many unsolved questions between light stimuli and flower responses.…”
Section: Use Of Light For Improving Cut Flower Qualitymentioning
confidence: 99%